Semantic Web materialization: a dynamic building model of queries based in ontology mapping - Coneglian, Caio Saraiva [UNESP]; Santarem Segundo, Jose Eduardo [UNESP] (Univ Federal Minas Gerais, Escola Biblioteconomia, 2018)
Approach the computer language to human language is a challenge in seeking to improve the process of information retrieval. From this perspective, the Semantic Web has allowed a new mode of data processing contained in the Web, in order to allow better understanding of the meaning that these information possess. However, some of the concepts involving the Semantic Web such as ontologies, have highly complex, making it difficult to use. The difficulty in understanding, the structure that they have, and diversity as they are built, make the ontologies manipulation to discover the meaning of the concepts, something not effective, making it impossible to offer a concrete overview of the meaning of the concepts. Thus, this research aims to propose a model that can verify the context and meaning of a term in an ontology. To this end, it performed bibliographic research, model building and implementation of a prototype as proof of concept for the verification of results. The model and implementation have resulted in the generic treatment of an ontology, to obtain the meaning and the context that has a term. Based on the results it is identified that the use of ontologies allows information systems to provide a broader perspective of the context of data, enabling informational user needs can be met more effectively.
Keywords: Semantic Web; Ontologies; SPARQL